iLearning Education Challenge: Combining the Power of Blockchain with Gamification Concepts - Surta Wijaya; Abigail Husain; Mackenzie Laurens; Andzelika Birgithri (CORISINTA, 2024)
The adoption of online learning in colleges as a response to the COVID-19 pandemic has profoundly influenced education. Knowledge acquisition dramatically depends on a person's interest and willingness to learn. A platform that fosters student motivation in effectively completing activity hours is required. The available learning strategies include collaborative and creative learning, which aim to attain successful graduation outcomes with the assistance of the Independent Campus program. This project aims to develop gamification strategies that enhance students' creativity, innovation, and interactivity by integrating principles of learning and play. Furthermore, blockchain-based learning platforms can be a regulatory mechanism for ensuring secure and pleasurable learning experiences while supporting esteemed educational institutions. By implementing gamification tactics in conjunction with blockchain technology, all devices linked to the network will be transformed into nodes or servers. This study employs agile development methodologies, namely iterative and incremental models, to design distributed storage blockchain algorithms. The GamiChain iLearning educational model, which incorporates gamification blockchain, is constructed using IPFS. GamiChain, a gamification blockchain, can effectively assist the Independent Campus initiative by providing students with the necessary resources to cultivate their potential and produce exceptional and successful graduates.